1991
DOI: 10.1039/c39910000057
|View full text |Cite
|
Sign up to set email alerts
|

Zeolite encapsulated Pd(salen), a selective hydrogenation catalyst

Abstract: Pd(salen) encapsulated in zeolites X and Y is shown t o be a catalyst for the selective hydrogenation of hex-l-ene in the presence of cyclohexene at 25 "C and 400 Torr HZ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(29 citation statements)
references
References 2 publications
0
29
0
Order By: Relevance
“…Numerous studies have been conducted on encapsulation of a variety of metal complexes [14,15], clusters [16,17] and organometallic compounds [9,18] in zeolitic hosts. Intensive studies have been considered to improve the catalytic properties for these materials in the oxidation of different types of organic substrates using alternative oxidation processes based on green and non-toxic oxidants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have been conducted on encapsulation of a variety of metal complexes [14,15], clusters [16,17] and organometallic compounds [9,18] in zeolitic hosts. Intensive studies have been considered to improve the catalytic properties for these materials in the oxidation of different types of organic substrates using alternative oxidation processes based on green and non-toxic oxidants.…”
Section: Introductionmentioning
confidence: 99%
“…It is observed that they cannot only retain their high activity and selectivity in homogeneous catalysis but also exhibit high stability. This is due to the reduction of degradation of the organic ligands and dimerization of the transition metal complexes in cavities [8][9][10][11][12][13], which could occur during homogeneous catalytic reactions, resulting in a reduction in the activity, and even irreversible deactivation.…”
Section: Introductionmentioning
confidence: 99%
“…The electronic spectrum of cobalt (II) neat complex is characterized by the highest energy 4 A 2 ? 4 T 1(P) transition at 658 nm is typical of tetrahedral Co(II) complexes [22].…”
Section: Electronic Spectral Studiesmentioning
confidence: 99%
“…These zeolite encapsulated metal complexes were used in various organic reactions like carbonylation, hydroformylation, hydrogenation, oxidation, hydroxylation etc. [2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…As this method can provide an ideal way for taking the advantages of homogenous catalysts and simultaneously avoid its disadvantages like handling and reusability. Encapsulation in porous solids such as zeolite is an attractive technique for heterogenization, since no leaching is observed when the complex is confined exclusively in the zeolite pores [13][14]. In addition, zeolite-encapsulated complexes promise better control of selectivity of the reaction and higher stability, due to NaY cavity encapsulated metal complexes, avoids direct contact with the metal complexes, reduced dimerization of complexes in the cavity.…”
Section: Introductionmentioning
confidence: 99%